Implementation of the Dimensions of Mutual Cooperation and Creativity in the Pancasila Student Profile in Indonesian Language Learning in Junior High Schools - Simanjorang, Agnes Insani Setiawati br; Rosari Dwimira Putri; Victoryel Barangan Andekan (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research examines the implementation of the dimensions of mutual cooperation and creativity in the Pancasila Student Profile in Indonesian language learning in junior high schools. Through a qualitative approach with direct observation methods, this research describes students' involvement in a descriptive text creation project, in the form of video blogs and vlog scripts, which aims to form cooperative and creative characters. The research results show that the implementation of Pancasila values ​​through these activities has succeeded in encouraging student collaboration and creativity. Collaborative activities help students practice communication, sharing ideas and working in teams, while their creativity is enhanced through the exploration of ideas in digital content production. This project plays a significant role in strengthening students' character in accordance with Pancasila values ​​and 21st century skills.